Bridging the Gap: How Social Entrepreneurs are Leveraging Creative Technologies to Address Community Challenges - Amina Intes; Guijiao Zou; Lie Jie (Journal of Social Entrepreneurship and Creative Technology, 2024)
Social entrepreneurs play a critical role in addressing community challenges by developing innovative solutions. The integration of creative technologies has further expanded the potential for these entrepreneurs to make a significant impact. This study investigates how social entrepreneurs are leveraging creative technologies to address various community challenges, examining the effectiveness and implications of these technologies in social entrepreneurship. The primary objective of this research is to explore the ways in which social entrepreneurs utilize creative technologies to tackle community issues. The study aims to identify key strategies, tools, and technologies that have been successful in creating positive social change. This research employs a mixed-methods approach, combining quantitative surveys and qualitative case studies. A survey was conducted with 200 social entrepreneurs to gather data on the types of creative technologies used and their perceived effectiveness. Additionally, in-depth case studies of five social enterprises were conducted to provide detailed insights into the implementation and impact of these technologies. The findings indicate that social entrepreneurs are increasingly adopting creative technologies such as augmented reality (AR), virtual reality (VR), and mobile applications to address community challenges. These technologies have been particularly effective in areas such as education, healthcare, and environmental sustainability. The case studies revealed that the successful use of creative technologies often involves a combination of innovative thinking, community engagement, and collaboration with tech experts. The study concludes that creative technologies offer significant potential for social entrepreneurs to address community challenges effectively. By leveraging these technologies, social entrepreneurs can enhance their impact, improve community engagement, and drive sustainable solutions. The research highlights the need for continued support and investment in creative technologies within the field of social entrepreneurship.